Tanggung Jawab Ilmuwan Pertanian Terhadap Dampak Penggunaan Pestisida ditinjau dari Aksiologi Ilmu - Rilliandi Arindra Putawa (Dinamika Lingkungan Indonesia, 2022)
The paradigm transition in agricultural science leaves many problems. The impact of using pesticides in the past has had a negative impact, both on the environment and on human life. Agricultural scientists as pesticide product developers should be responsible for their scientific products' impact. This research is a philosophical study that aims to analyze the responsibility of scientists on the phenomenon of pesticide use by using the axiology of science. This research is a philosophical reflection on the development of pesticides in agriculture as a controversial issue, both structurally and normatively. The results show that there are two responsibilities of agricultural scientists that can be contradictory: social responsibility to meet the community’s food needs and moral responsibility to pay attention to the environmental impacts caused.